2021
DOI: 10.3390/molecules26092566
|View full text |Cite
|
Sign up to set email alerts
|

Berberrubine Phosphate: A Selective Fluorescent Probe for Quadruplex DNA

Abstract: A phosphate-substituted, zwitterionic berberine derivative was synthesized and its binding properties with duplex DNA and G4-DNA were studied using photometric, fluorimetric and polarimetric titrations and thermal DNA denaturation experiments. The ligand binds with high affinity toward both DNA forms (Kb = 2–7 × 105 M−1) and induces a slight stabilization of G4-DNA toward thermally induced unfolding, mostly pronounced for the telomeric quadruplex 22AG. The ligand likely binds by aggregation and intercalation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
(151 reference statements)
0
3
0
Order By: Relevance
“…Moreover, in the same study, they also investigated the orientation of the ligand with G4s by analyzing the ICD signals [ 137 ]. The same research group reported the binding modes of a selective fluorescent probe of DNA G4s [ 138 ].…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
“…Moreover, in the same study, they also investigated the orientation of the ligand with G4s by analyzing the ICD signals [ 137 ]. The same research group reported the binding modes of a selective fluorescent probe of DNA G4s [ 138 ].…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
“…Berberine has a long history of use in traditional Chinese medicine, and its anticancer activity is related to its binding to DNA . Berberine and derivatives bind G-quadruplex (G4) DNA structures with higher affinity than duplex DNA. As such, the G4-binding of berberine has been extensively studied. Berberine has an asymmetric scaffold of four fused rings with a methylenedioxy group at one end (ring A) (Figure C).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the fluorescence emission of these solutions was recorded by exciting at 443 nm (at the isosbestic point observed in the UV/Vis spectra, where both the free berberine and the complex have the same extinction coefficient, see Figure 2 ) and collecting the emission at λ max (~536 nm). Fluorescence spectroscopy was chosen to follow the binding because berberine is almost not fluorescent in aqueous solution, whereas a strong fluorescence increase is observed upon binding to G4Qs [ 28 , 29 ]. Thus, the fluorescence intensity is directly related to complex formation.…”
Section: Resultsmentioning
confidence: 99%